Metode Hadis Shahih dalam Perspektif Muhammadiyah - Wahid, Abd; Masbur; Mukminin, Jamalul (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This study is categorized as library research, focusing on the methodologies employed by Muhammadiyah in determining the authenticity of hadiths. The research adopts a descriptive-analytic method, which involves identifying, analyzing, and clarifying issues to systematically and accurately depict the characteristics of the problem at hand. The findings reveal that Muhammadiyah utilizes the tarjih method. Tarjih refers to the process of preferring one of two conflicting hadiths that cannot be reconciled and designating the other as marjuh, based on specific reasons for tarjih. In the application of tarjih, Muhammadiyah has established 11 fundamental concepts for determining the authenticity of a hadith. This method involves a meticulous examination of both the matan (content) and the sanad (chain of narration). Furthermore, to address conflicts between hadiths, Muhammadiyah has developed resolution principles using the ta'arud al-adillah method. This methodological framework ensures a comprehensive and systematic approach to validating hadiths, emphasizing the importance of contextual and textual integrity. Through these rigorous processes, Muhammadiyah aims to provide a balanced and credible interpretation of Islamic teachings.